2014
DOI: 10.1186/1471-2393-14-150
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation during pregnancy: summary of experimental studies suggesting a treatment to improve fetal and neonatal morbidity and reduce mortality in high-risk human pregnancy

Abstract: While the use of creatine in human pregnancy is yet to be fully evaluated, its long-term use in healthy adults appears to be safe, and its well documented neuroprotective properties have recently been extended by demonstrations that creatine improves cognitive function in normal and elderly people, and motor skills in sleep-deprived subjects. Creatine has many actions likely to benefit the fetus and newborn, because pregnancy is a state of heightened metabolic activity, and the placenta is a key source of free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 125 publications
(150 reference statements)
1
47
0
1
Order By: Relevance
“…Creatinine excretion during pregnancy was shown to decrease, as also observed in this study, as well as levels in serum due to increased glomerular filtration rate [23]. Interestingly, creatine supplementation during pregnancy was recently proposed to have benefits for the fetus and neonate whenever oxidative stress or feto-placental hypoxia arise [40]. Previous assessment of early fetal growth using multiple ultrasound measures found that size at birth does not correspond to fetal growth rate, as confirmed in our data [41].…”
Section: Discussionsupporting
confidence: 58%
“…Creatinine excretion during pregnancy was shown to decrease, as also observed in this study, as well as levels in serum due to increased glomerular filtration rate [23]. Interestingly, creatine supplementation during pregnancy was recently proposed to have benefits for the fetus and neonate whenever oxidative stress or feto-placental hypoxia arise [40]. Previous assessment of early fetal growth using multiple ultrasound measures found that size at birth does not correspond to fetal growth rate, as confirmed in our data [41].…”
Section: Discussionsupporting
confidence: 58%
“…Thus, gender-specific research with creatine is developing into a very interesting topic that deserves specific attention in the future [see also the publication by Kondo et al (2016), who describe gender-specific positive effects of creatine for young women with severe depression]. This review is then followed by original work of the same group showing that maternal dietary creatine supplementation during pregnancy in a rodent animal model, the spiny mouse, protected the neonate from multi-organ damage, if birth was taking place under conditions with intrapartum hypoxia and birth asphyxia (Dickinson et al 2014). Since the effects of nutritional supplementation during pregnancy must be subject to careful investigation, Ellery et al (2016b) again used the spiny mouse model and fed mid-gestation pregnant and virgin spiny mice with a rather high dose of 5 % w/w creatine in the chow for 18 days, followed by analysis of the expression pattern of the two enzymes involved in endogenous creatine synthesis, AGAT and GAMT, as well as of the creatine transporter (CrT).…”
Section: Creatine In Healthmentioning
confidence: 99%
“…In adults, approximately one-half of the daily requirement for creatine comes from meat, fish, and other animal products in the diet; the remainder is derived from endogenous synthesis from arginine, glycine, and methionine (28). Creatine is involved in cellular energy production, but it also has neuroprotective effects (29).…”
Section: Discussionmentioning
confidence: 99%
“…Creatine synthesis consumes 20-30% of arginineÕs amidino groups, and therefore imposes an appreciable burden on the metabolism of arginine (28). In adults, approximately one-half of the daily requirement for creatine comes from meat, fish, and other animal products in the diet; the remainder is derived from endogenous synthesis from arginine, glycine, and methionine (28).…”
Section: Discussionmentioning
confidence: 99%